2007
DOI: 10.1016/j.regpep.2006.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Lack of obestatin effects on food intake: Should obestatin be renamed ghrelin-associated peptide (GAP)?

Abstract: Obestatin is a newly identified ghrelin-associated peptide (GAP) that is derived from post-translational processing of the prepro-ghrelin gene. Obestatin has been reported initially to be the endogenous ligand for the orphan receptor G protein-coupled receptor 39 (GPR39), and to reduce refeeding- and ghrelin-stimulated food intake and gastric transit in fasted mice, and body weight gain upon chronic peripheral injection. However, recent reports indicate that obestatin is unlikely to be the endogenous ligand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 40 publications
2
56
0
2
Order By: Relevance
“…Moreover, our data reveal that the effect of peripherally administered obestatin on food intake in rats depends neither on time in the circadian rhythm when the experiment is conducted, nor on the metabolic conditions of the experimental animals. The present findings are also consistent with the lack of effect of peripherally administered obestatin on gastric motor function as assessed by monitoring changes in gastric motility or emptying in both rats and mice [3,11,14,16,17] contrasting with the initial report [51].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, our data reveal that the effect of peripherally administered obestatin on food intake in rats depends neither on time in the circadian rhythm when the experiment is conducted, nor on the metabolic conditions of the experimental animals. The present findings are also consistent with the lack of effect of peripherally administered obestatin on gastric motor function as assessed by monitoring changes in gastric motility or emptying in both rats and mice [3,11,14,16,17] contrasting with the initial report [51].…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest that obestatin may be involved in the regulation of energy homeostasis in rodents. However, several recent studies performed in rats and mice under various experimental conditions showed that obestatin injected intraperitoneally (ip) has no inhibitory effect on short-term food intake [11,[14][15][16][17]21,32,41,54] and body weight gain [32,42]. The responsiveness to exogenous obestatin could be influenced by circadian rhythm and might account for the varying effects of peripheral obestatin on food intake found in recent studies [7,15,18,21,27,32,[40][41][42]51,54].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicating the lack of obestatinimpact on food intake are related to fasted-rodents which is a condition associatedwith the highest endogenous circulating levels of ghrelin [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The putative natural ligand for GPR39 was suggested to be an amidated 23-amino acid (aa) peptide designated as obestatin isolated from rat stomach (Zhang et al 2005). However, recent studies failed to demonstrate that obestatin could bind and activate GPR39 (Lauwers et al 2006, Chartrel et al 2007, Gourcerol et al 2007. It was suggested that the impure obestatin used in the original report might be responsible for the aberrant results (Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%